Assessment of Rheumatoid Arthritis in Clinical Care - Tuulikki Sokka, (Archives of Rheumatology, 2010)
Quantitative clinical monitoring of patients with musculoskeletal conditions should be included in the infrastructure of every clinical practice. Quantitative monitoring improves the physician’s capacity to assess and document a patient’s clinical status and changes over time, which leads to greater accuracy in the underlying rationale for clinical decisions. Furthermore, routine data collection in consecutive patients facilitates analyses of groups of patients over long periods in usual care, beyond information that can be obtained from randomized clinical trials. (Turk J Rheumatol 2010; 25: 1-11)